2005
DOI: 10.1002/syn.20189
|View full text |Cite
|
Sign up to set email alerts
|

[11C]MADAM, a new serotonin transporter radioligand characterized in the monkey brain by PET

Abstract: The aim of this study was to explore the potential of a new selective serotonin transporter (5-HTT) inhibitor, N,N-dimethyl-2-(2-amino-4-methylphenylthio)benzylamine (MADAM, K(i)=1.65 nM), as a PET radioligand for examination of 5-HTT in the nonhuman primate brain. MADAM was radiolabeled by an N-methylation reaction using [(11)C]methyl triflate and the binding was characterized by PET in four cynomolgus monkeys. Metabolite levels in plasma were measured by gradient high-performance liquid chromatography (HPLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…As it has already been shown in previous non-human primate PET studies [18], the regional distribution of radioactivity in the brain following administration of [ 11 C]MADAM was consistent with the known regional densities of SERT sites. Following the administration of [ 11 C]MADAM a total brain uptake of approximately 6% of the injected dose was measured ( Figure 4A).…”
Section: Accepted Manuscriptsupporting
confidence: 79%
See 1 more Smart Citation
“…As it has already been shown in previous non-human primate PET studies [18], the regional distribution of radioactivity in the brain following administration of [ 11 C]MADAM was consistent with the known regional densities of SERT sites. Following the administration of [ 11 C]MADAM a total brain uptake of approximately 6% of the injected dose was measured ( Figure 4A).…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…Among them, [ 123 I]ADAM is the current SPECT radioligand [10][11][12] and for PET studies, [ 11 C]DASB and [ 11 C]MADAM ( Figure 1) have been shown to be appropriate radioligands for the in vivo investigation of SERT [13][14][15][16][17][18][19]. this radioligand [18,19]. The percentage of the unchanged radioligand [ 11 C]MADAM in human plasma was about 40% at 50 min after radioligand injection [19].…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 C]MADAM binds selectively to 5-HTT (Halldin et al 2005; Lundberg et al 2005), has good reliability in measurements of 5-HTT binding in vivo in the human brain (Lundberg et al 2006) and has been shown to be suitable for occupancy studies (Lundberg et al 2007 a ). …”
Section: Introductionmentioning
confidence: 99%
“…regulation gene transcription)[ 18 F]setoperoneBlin et al [6][ 18 F]altanserinLemaire et al [14][ 11 C]MDL-100907Lundkvist et al [15][ 18 F]MH.MZHerth et al [10]5-HT 4 Excitatory receptor[ 11 C]SB207145Marner et al [17]SERTReuptake transporter (e.g. target SSRI)[ 11 C]McN5652Suehiro et al [24][ 11 C]DASBHoule et al [11][ 11 C]MADAMHalldin et al [9][ 18 F]ADAMMa et al [16]TrpPrecursor 5-HTP and substrate TPHα-[ 11 C]methyltryptophanDiksic et al [7]5-HTPPrecursor 5-HT and substrate AADC5-hydroxy- L -[β- 11 C]tryptophanBjurling et al [5]…”
Section: Introductionmentioning
confidence: 99%